The effect of the 'Maane Al Koran' le abi ishaq Al zagag(311h) in book "kashif Almushkilat and Idah Alme'edilat" le jamea Al uloum Al baquoly(542h) - عطا موعد, محمد; غليون, فاطمة (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The study aims to search the sources at Albaquoly's book kashif Almushkilat and Idah Alme'edilat, it is of many sides book; so hat, I concentrated on only one side called showing the effect that produced by Alzagag. The value of this study is existed in the gathering two honorable syntax specialists, they howe clear effect in supporting the scientific linguistic movement.